(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Fatma Alije (1862–1936) is the first Turkish female novelist. She is the daughter of the celebrated historian, lawyer, theologian and statesman Ahmet Dževdet-Pasha who was a prototype of the conservative intellectual, but also a state reformer. Both his daughters, Fatma Alije and Emine Semije acquired significant education, the knowledge of French, philosophy, literature and art. Fatma Alije wrote five novels and several articles dedicated mostly to the issue of the position of women in the traditional Turkish society. This paper will be dedicated to her first independent novel, Razgovori (Talks), published in 1891, in which, for the first time in Turkish history, a woman wrote about the intimate world of women, first love, freedom of choice. Although she courageously put forward the question of women’s emancipation, Fatma Alije remained devoted to the traditional Islamic view of the world and the position of women. Despite the little value placed upon her work, Fatma Alije set the foundation of Turkish women’s literature. Her work represents a crucial source for the study of Turkish women’s literature which has until today produced various eminent names and works. Although the historians of Turkish literature forgot about Fatma Alije or purposely left her out for a significant amount of time, it is evident that recently this author has been receiving more and more attention in Turkey.